2008
DOI: 10.1353/jod.2008.0032
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion and Democratic Legitimacy

Abstract: This paper examines on a global scale how important it is for young democracies to deliver economic welfare to win the hearts of their citizens. A decoupling of popular support for democratic form of government from economic performance is believed to be conducive to the consolidation of young democracies. We found an encouraging global pattern that clearly shows evaluations of economic condition are relatively unimportant in explaining level of popular support for democracy. However, high-income East Asian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 11 publications
0
72
1
1
Order By: Relevance
“…Typically, the respondents are asked to choose among three statements: (1) Democracy is always preferable to any other kind of government; (2) Under some circumstances, an authoritarian government can be preferable to a democratic one; and (3) For people like me, it does not matter whether we have a democratic or a nondemocratic regime. This has been the most widely used item due not only to its face validity, but also to the way in which it facilitates meaningful comparison (Chu, Bratton, Lagos, Shastri, & Tessler, 2008). Similar to previous research, this study codes the respondents" answers to this survey question as 1 for those who think of democracy as the best political system all the time and 0 otherwise.…”
Section: Support For Democracymentioning
confidence: 91%
See 1 more Smart Citation
“…Typically, the respondents are asked to choose among three statements: (1) Democracy is always preferable to any other kind of government; (2) Under some circumstances, an authoritarian government can be preferable to a democratic one; and (3) For people like me, it does not matter whether we have a democratic or a nondemocratic regime. This has been the most widely used item due not only to its face validity, but also to the way in which it facilitates meaningful comparison (Chu, Bratton, Lagos, Shastri, & Tessler, 2008). Similar to previous research, this study codes the respondents" answers to this survey question as 1 for those who think of democracy as the best political system all the time and 0 otherwise.…”
Section: Support For Democracymentioning
confidence: 91%
“…First of all, some studies have found the close relationship between institutions and democracy (Huntington, 1968;Anderson & Guillory, 1997;O"Donnell, 1998), and Chu et al (2008) found that the levels of trust that people feel toward parliament, parties, and courts have an influence on people"s attitude toward democracy. As a result, it is necessary to control the effect of people"s trust in political institutions when it comes to support for democracy.…”
Section: Control Variablesmentioning
confidence: 99%
“…For example, Kunovich (2013) concluded that misperceptions of unemployment led to changes in political and economic attitudes, while actual rates of unemployment were not directly related to changes in people's attitudes. Moreover, other authors found that the perceived economic performance of the country has an effect on people's democratic attitudes (Chu, Bratton, Lagos, Shastri and Tessler 2008). In addition, there are effects found of perceived corruption in people's support for democratic ideals (Chang and Kerr 2009) and in people's trust in institutions as well as attitudes towards gift giving (Melgar, Rossi and Smith 2010).…”
Section: Rationalit Y Values and Beliefs: Individual-level Explanatimentioning
confidence: 98%
“…In line with this logic, Diamond (1999) specifies that democracy can only be effective and stable if more than 70% of citizens consider it preferable and, at the same time, less than 15% of the population would opt for a nondemocratic alternative if a democratic government failed to meet their expectations and dealt ineffectively with imminent socioeconomic and political problems. In this respect, Chu et al (2008) deplore that fewer than half of emerging democracies meet these standards, rendering third-wave democratization prone to "democratic recession" (Chu, Diamond, Nathan, & Shin, 2009:155).…”
Section: Introductionmentioning
confidence: 99%